2014
DOI: 10.1111/cdev.12260
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations Among Parents' Reactions to Children's Negative Emotions, Effortful Control, and Math Achievement in Early Elementary School

Abstract: Panel mediation models and fixed-effects models were used to explore longitudinal relations among parents' reactions to children's displays of negative emotions, children's effortful control (EC), and children's math achievement (N = 291; M age in fall of kindergarten = 5.66 years, SD = .39 year) across kindergarten through second grade. Parents reported their reactions and children's EC. Math achievement was assessed with a standardized achievement test. First-grade EC mediated the relation between parents' r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 95 publications
5
22
0
Order By: Relevance
“…Specifically, we first examined the separate , or individual, effect of each LRS construct on reading and math achievement, above the covariates. Consistent with previous research (Swanson, Valiente, Lemery-Chalfant, Bradley, & Eggum-Wilkens, 2014; Valiente et al, 2008), we expected that, when considered separately, each LRS construct would predict reading and math achievement, above relevant demographic covariates (i.e., gender, IQ, and economic adversity). Next, we examined the joint contributions of the LRS constructs to children's reading and math achievement when considered simultaneously .…”
Section: Purpose Of This Studysupporting
confidence: 75%
See 1 more Smart Citation
“…Specifically, we first examined the separate , or individual, effect of each LRS construct on reading and math achievement, above the covariates. Consistent with previous research (Swanson, Valiente, Lemery-Chalfant, Bradley, & Eggum-Wilkens, 2014; Valiente et al, 2008), we expected that, when considered separately, each LRS construct would predict reading and math achievement, above relevant demographic covariates (i.e., gender, IQ, and economic adversity). Next, we examined the joint contributions of the LRS constructs to children's reading and math achievement when considered simultaneously .…”
Section: Purpose Of This Studysupporting
confidence: 75%
“…Next, we examined the joint contributions of the LRS constructs to children's reading and math achievement when considered simultaneously . Based on previous studies (Swanson et al, 2014; Valiente et al, 2008; Zhou, Main, & Wang, 2010), we expected that EC would emerge as a stronger predictor of math versus reading. Furthermore, based on the moderate to strong association between measures of BSR and SC, and the finding that only BSR has an independent effect on achievement (Hughes et al, 2008), we expected that only EC and BSR would make independent contributions to reading and math achievement.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…For example, Bohlmann, Maier, and Palacios (2015) found a bidirectional association between effortful control and expressive language in the transition from preschool to kindergarten (but not across preschool), which has implications for later academic achievement. Similarly, Swanson, Valiente, Lemery-Chalfant, Bradley, and Eggum-Wilkens (2014) reported that math achievement (assessed in the spring term of kindergarten) predicted parent-reported effortful control (assessed in the fall term of first grade) in the transition from kindergarten to first grade, and vice versa from first to second grade. Future research should consider similar bidirectional pathways between effortful control and academic-related skills, as this has implications for the development of prevention programs designed to improve both academic and behavioral adjustment.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we examined the temporal sequence linking victimization, depression, and achievement over three time points in a sample of Chinese primary school students. In order to determine more precisely the nature and direction of the associations, we followed previously established protocols (e.g., van Lier et al ., ; Swanson, Valiente, Lemery‐Chalfant, Bradley, & Eggum‐Wilkens, ) and examined four specific competing models. Model 1 was autoregressive and included stability paths between repeated measures.…”
Section: Introductionmentioning
confidence: 99%